Colgajo de recto anterior del abdomen para el tratamiento de los defectos de cobertura lumbosacros. [Rectus abdominis flap for the treatment of lumbosacral coverage defects.] - Franco L. De Cicco; Mariano O. Abrego; Gerardo L. Gallucci; Pablo De Carli; Jorge G. Boretto (Revista de la Asociación Argentina de Ortopedia y Traumatología, 2018)
Introduction: Treatment of soft tissue lumbosacral defects is based on dead space management and defect coverage. The aim of this study is to describe the surgical technique, results and complications of patients who underwent rectus abdominis flap for lumbosacral defects coverage.Methods: A six-year retrospective review was performed. Demographic characteristics are analyzed. Surgical technique and intra-operative complications are described. Postoperative variables, such as donor site complications, recipient site complications, and flap survival were also reported. Results: Five patients met the inclusion criteria (average age, 50 years). Four patients presented sacral tumor diagnosis and one patient had lumbosacral osteomyelitis. Mean follow-up was 20 months. Flap average size was 8 x 13 cm. Intraoperative complications were one pedicle injury (microsurgical repair) and the death of a patient. Regarding postoperative complications, one wound dehiscence was reported. None of the flaps suffered vascular complications and all remained vital throughout follow-up.Conclusion: Rectus abdominis flap should be considered a valid option in the management of large soft tissue lumbosacral defects. This flap provides sufficient skin volume and muscular tissue. Surgical technique is relatively simple with no need for microsurgical procedure.